Deleterious effects of chronic alcohol use on human organic function: an integrative literature review (Research, Society and Development, 2022)
Introduction: Excessive consumption of alcoholic beverages is considered the fifth most important risk factor for the occurrence of premature deaths and disabilities in the world, including liver, nutritional and certain types of cancer, in addition to causing chemical dependence and facilitating the occurrence. of violence and accidents. Objective: to elucidate the deleterious effects of alcohol on human organic function. Methodology: this is a descriptive research of the integrative literature review type. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services. Results and discussion: the harmful use of alcohol can affect various parts of the body, causing diseases such as cancer, pancreatitis, liver disease, gastrointestinal problems, peripheral neuropathy, heart and vascular problems, brain damage and immune dysfunctions. Excessive and continued consumption of alcohol increases the risk for health complications. Final considerations: the effects of alcohol on each individual are different and depend on a number of factors, even when consumed in equal amounts.